Molten Ag2SO4‐based Ion‐Exchange Preparation of Ag0.5La0.5TiO3 for Photocatalytic O2 Evolution. Issue 8 (27th March 2017) - Zong, Shichao; Cheng, Cheng; Shi, Jinwen; Huang, Zhenxiong; Hu, Yuchao; Yang, Honghui; Guo, Liejin
Abstract: Ag0.5 La0.5 TiO3 with an ABO3 perovskite structure was synthesized by a newly developed ion‐exchange method. Molten Ag2 SO4 instead of traditional molten AgNO3 was used as Ag + source in view of its high decomposition temperature (1052 °C), thereby guaranteeing the complete substitution of Ag + for Na + in Na0.5 La0.5 TiO3 with a stable ABO3 perovskite structure at a high ion‐exchange temperature (700 °C). Under full‐arc irradiation, the O2 ‐evolution activity of Ag0.5 La0.5 TiO3 was about 1.6 times that of Na0.5 La0.5 TiO3 due to the optimized electronic band structures and local lattice structures. On the one hand, the substitution of Ag + for Na + elevated the VBM and thus narrowed the band gap from 3.19 to 2.83 eV, thereby extending the light‐response range and, accordingly, enhancing the photoexcitation to generate more charge carriers. On the other hand, the substitution of Ag + for Na + induced a lattice distortion of the ABO3 perovskite structure, thereby promoting the separation and migration of charge carriers. Moreover, under visible‐light irradiation, Ag0.5 La0.5 TiO3 displayed notable O2 evolution whereas Na0.5 La0.5 TiO3 showed little O2 evolution, thus demonstrating that the substitution of Ag + for Na + enabled the use of visible light to evolve O2 photocatalytically. This work presents an effective route to explore novel Ag‐based photocatalysts. Abstract : Evolution at work : Ag0.5 La0.5 TiO3, synthesized by a newly developed ion‐exchange method using molten Ag2 SO4 as Ag + source, showed improved photocatalytic activity for O2 evolution.